2006
DOI: 10.1111/j.1533-2500.2006.00068.x
|View full text |Cite
|
Sign up to set email alerts
|

Occipital Nerve Blockade for Cervicogenic Headache: A Double‐Blind Randomized Controlled Clinical Trial

Abstract: Cervicogenic headache is a chronic hemicranial pain, usually occurring daily. This randomized, double-blind, placebo-controlled trial evaluated the effectiveness of nerve stimulator-guided occipital nerve blockade in the treatment of cervicogenic headache. The reduction in analgesic consumption was the primary outcome measure. Fifty adult patients diagnosed with cervicogenic headache were randomly divided into two equal groups of 25 patients each. All patients in both groups received greater and lesser occipit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 25 publications
4
85
0
2
Order By: Relevance
“…The greater occipital nerve can be easily blocked and serves as important diagnostic evidence if a temporary relief is obtained [81,82]. A greater occipital nerve block study in CeH showed significant improvement after 2 weeks [83]. The C3 level may be effectively blocked reducing the pain stemming from the C2-C3 zygapophysial joint [84].…”
Section: Treatmentmentioning
confidence: 97%
“…The greater occipital nerve can be easily blocked and serves as important diagnostic evidence if a temporary relief is obtained [81,82]. A greater occipital nerve block study in CeH showed significant improvement after 2 weeks [83]. The C3 level may be effectively blocked reducing the pain stemming from the C2-C3 zygapophysial joint [84].…”
Section: Treatmentmentioning
confidence: 97%
“…Naja et al [17] performed a double-blind, placebo-controlled trial of GONB with fentanyl, bupivacaine, clonidine, and lidocaine. The primary end point was analgesic consumption at 2 weeks, which was significantly lower for the lidocaine group than for the placebo group.…”
Section: Introductionmentioning
confidence: 99%
“…The lesser occipital nerve arises from the second cervical spinal nerve and sometimes the third and supplies sensation to the skin lateral to the GON and posterior to the greater auricular nerve. Blockade of these nerves with local anesthetic with or without steroids has been used to treat many different headache disorders including migraine, [96][97][98][99] cluster headache, 100-106 chronic daily headache, 100,107-109 hemicrania continua, 100,110 trigeminal neuralgia, 111 cervicogenic headache, 97,[112][113][114][115][116] and postdural puncture headache. 117,118 Although the results from most of the reported case series and studies are favorable, there is currently little convincing evidence for the efficacy of GON blockade in the acute or preventive treatment of headache, as most data on this topic come from noncontrolled studies.…”
Section: Occipital Nerve Blocksmentioning
confidence: 99%